Skepticism as a Mediating Mechanism in the Relationship between Sustainability Literacy and Students' Green Consumption Behavior - Muhammad Shidiq Al Mutawakkil; Muhammad Taufik; Nurbiah; Linda Arisanty Razak; Ismail Badollahi (Journal of Management, Economic, and Accounting, 2026)
This study examines the influence of sustainability literacy on green consumption behavior among university students and tests the mediating role of green skepticism. Using a quantitative explanatory approach with a cross-sectional survey of 100 active students at Indonesian universities, data were analyzed via PLS-SEM (SmartPLS). Outer model evaluation confirmed convergent validity (factor loading ≥ 0.651; AVE > 0.59) and construct reliability (CR > 0.94; CA > 0.93). Inner model results demonstrate: sustainability literacy positively and significantly affects green consumption behavior (β = 0.484; t = 5.480; p < 0.001) and green skepticism (β = 0.648; t = 8.150; p < 0.001); green skepticism positively and significantly affects green consumption behavior (β = 0.386; t = 4.120; p < 0.001); and green skepticism partially mediates the relationship (β indirect = 0.250; 95% CI = [0.146; 0.352]). R² = 0.625 indicates substantial predictive power. Findings confirm that knowledge-based green skepticism functions as a catalyst for selective green consumption, not a barrier.